New Ventures: Marketing Challenges and need for Entrepreneurial Marketing - Sharma, Sourabh (2010)
Gamingdom is a new start up venture that provides online gaming services in India, utilizing the latest cloud computing technology. The gaming industry in India is expected to grow in the next 5 years, and we a team of budding entrepreneurs are making an attempt to cash-in on the opportunity using the advantages of latest technology – Cloud Computing. Marketing is an important aspect of any business but new ventures do need an entrepreneurial mindset in marketing in order to have long term sustainability, because of the different set of challenges that new ventures face as compared to existing and established businesses. This write up looks into the Marketing methods adopted by the team in the proposal for Gamingdom business and also providing an insight into challenges faced by start up businesses and Entrepreneurial Marketing in detail.